Educational Change Beyond Borders: International Baccalaureate in New Zealand - Hara, Kazuhisa (Auckland University of Technology, 2011)
The International Baccalaureate Organization (IBO) provides three international education programmes for schools: the Primary Years Programme, the Middle Years Programme, and the Diploma programme. These programmes were developed originally for students attending international schools. However, it has been observed that the programmes were also being used in national schools (i.e., state schools, state-funded private schools, and nationally-located private schools), and that the number of such schools has increased significantly over the years. This study explored the perspectives of school leaders and teachers on the implementation of the International Baccalaureate (IB) programmes in New Zealand (NZ) schools by inquiring (1) why some schools adopted the programmes; (2) how they implemented the programmes; (3) what the adoption process looked like; and (4) what influence the implementation of the IB had on teachers’ professional practices. The research project employed a qualitative approach because the purpose of this study was to gain an understanding about shared meanings attached to the IB programmes in the context of the NZ education system. The researcher approached all NZ IB schools (both authorised and candidate schools) to recruit research participants. Overall, 37 people who were either school leaders or teachers participated in the research. Semi-structured interviews were employed as the primary data-collection method in this study. Document analysis complemented the interview data. Data collection occurred over a period of one year (December 2008–December 2009), during which the researcher visited and interviewed research participants one by one. Qualitative data analysis was conducted and emerging themes were examined to capture the unique experiences of school leaders and teachers. The research data suggested that the people who worked in IB schools in New Zealand attached various meanings to the IB programmes beyond the IB founders’ intentions. Although fostering greater internationalism in school communities is the raison d’être of the IBO, the evidence from this study suggested that the driving factor behind the introduction of the IB into NZ schools was the school leaders’ practical needs and desires to make their schools more attractive and accountable to parents, teachers, and students, and to gain a better position in the NZ education market. This research also found that how schools localised the programmes in curriculum content and delivery structures reflected the reasons why they offered the IB programmes. As the IBO website states, while the organisation forms a worldwide community of the IB schools there is no such thing as a typical IB school. As for the adoption process, the research findings indicated that most of the IB schools in New Zealand seemed to have experienced five salient stages: knowledge, persuasion, decision-making, implementation, and reinforcement and networking. The process was similar to the innovation-decision model developed by Everett M. Rogers (2003). All teachers who participated in the research seemed to have had positive experiences with the IB programmes. The research study contributes to widening the knowledge base of international education by helping to clarify how schools utilise the IB programmes to enhance their educational offerings in the NZ context.
Keywords: International Baccalaureate; Diploma programme; Middle Years Programme; Primary Years Programme; International Education; New Zealand; Diffusion of Innovations